Validity of an inertial device for measuring linear and angular velocity in a leg extension exercise - Pino-Ortega, J.; Bastida-Castillo, A.; Hernández-Belmonte, A.; Gómez-Carmona, C. D. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2020)
Traditionally, linear transducers have been used to evaluate resistance exercise with linear displacement. The current problem is the assessment of exercises with curvilinear displacement. For this reason, new devices should be assessed during training sessions. The purpose was to evaluate (1) the concurrent validity of mean linear velocity and (2) the convergent validity of mean angular velocity measured by an inertial device during a leg extension exercise. Ten elite-level football players completed six series of five repetitions of a leg extension exercise. WIMU PRO™ inertial device and GymAware® linear transducers as criterion measure were used to register data. To assess concurrent validity, the bias of the inertial device measures of velocity was analyzed with Bland-Altman plots with limits of agreement set at 95%. Convergent validity of inertial device measures of velocity was assessed with Pearson`s correlation analysis. Concurrent analysis showed a nearly perfect validity between linear transducers and inertial device in linear (Bias = -0.011 ± 0.006) and angular velocity (-0.34 ± 2.08). A nearly perfect Pearson`s product-moment correlation coefficient between an inertial device and linear transducers in linear velocity (r = 0.999) and between an inertial device and linear transducers (calculated) in angular velocity (r = 0.999) was found. In conclusion, WIMU PRO is valid for measuring linear and angular velocity during two-dimensional linear and rotational motions of exercise equipment. This device can be used as a useful tool to assess movement velocity in resistance training exercises, even in curvilinear movements when linear transducers have obvious limitations.